Atividade antifúngica in vitro de Extrato da Própolis Vermelha de Alagoas em Candida spp. isoladas de pacientes com Candidíase Vulvovaginal - Almeida, Geone Pimentel dos Santos Bulhões de (2017)
Vulvovaginal candidiasis (VVC) is a fungal infection classified as a sexually transmitted disease according to WHO, caused by yeast of the genus Candida. In Brazil, it is the second cause of infections among women of childbearing age and sexually active. The therapeutic treatment available for VVC treatment is restricted to polyene and azole drugs and resistance to the recommended antifungal agents (ketoconazole / CET, fluconazole / FLU, itraconazole / ITR and nystatin / NIS) has been reported more frequently in Candida albicans , the main associated species, but also in Candida non-albicans species (eg C.glabrata, C. krusei and C. parapsilosis complex). Propolis is a resinous compound produced by bees Apis mellifera L. and is known to possess a variety of biological activities, and Brazilian red propolis (BRP) has components such as flavonoids that cause structural and functional damage against microorganisms. The objective of this study was to evaluate the in vitro antifungal activity of PVA (ethanol extract and fractions) against different Candida species, focusing on clinical isolates of VVC. Five strains of ATCC reference (C. albicans, C. glabrata, C. tropicalis, C. parapsilosis and C. krusei) and 15 clinical isolates (3 of each species) were cultured from patients with VVC from Maceió / Alagoas on Sabouraud agar Dextrose and CHROMagar® Candida separately until 48 hours at 37° C. Suspensions of individual Candida cultures were adjusted to 0.5 McFarland standard in 0.9% NaCl solution for antimicrobial susceptibility testing (TSA) by disc diffusion and microdilution methods, as CLSI for CET, ITR, FLU , NIS, as well as EE and its fractions. The JASP (version 0.8.3.1) and IBM®SPSS (version 23.0) programs were adopted in the statistical analyzes. It was observed that in the TSA by disk diffusion and microdilution with both commercial antifungal and EE and fractions showed varied susceptibility profiles for the analyzed species, mainly among the clinical isolates when compared to the reference strains. By the disc-diffusion method all ATCC strains were susceptible to CET and NIS, but there was resistance to ITR and FLU mainly in C. glabrata and C. krusei, including ITR / FLU co-resistance pattern confirmed in 9 isolates. Among all the clinical isolates, resistance to at least 2 antifungal agents was tested, being 8 resistant to CET / ITR / FLU, drugs indicated by RENAME (SUS) for VVC treatment. The microdilution tests confirmed that CET and NIS were more effective, whereas FLU and ITR had less activity in the reference strains and some clinical isolates. The microdilution method with PVA showed MICs for the fractions ranging from 125 to 250 μg / mL, being found MIC of 500 μg / m only for C. parapsilosis and C. krusei in relation to the hexanolic and ethanolic fractions, respectively. The ethanolic fraction of PVA was effective against a larger number of strains tested, but the acetanolic fraction acted with lower MIC, probably because of more flavonoids, whereas the chloroform fraction had homogenous MIC among the reference strains (250 μg / mL) . TSA by both methods indicated 9 clinical isolates with ITR / FLU co-resistance, and PVA was effective with low MIC for 6 isolates with R-ITR / FLU standard. Disk-diffusion and microdilution tests were concordant in most of the strains and isolates tested. These results provide new data on the Brazilian red propolis of Alagoas in relation to the quality of flavonoids and confirmed the anti-Candida activity of different fractions for several species frequently involved in vulvovaginal candidiasis, creating possibilities for the use of PVA as a bioactive with important pharmacological potential in formulations of vaginal use.